Innovation in Islamic social finance for sustainable impact - Omar, Najiha; Che Man, Norajila (Journal of Islamic, Social, Economics and Development, 2025)
Islamic social finance generates a positive social and economic impact by utilizing instruments that align with Maqasid Shariah. Instruments such as waqf, zakat and sadaqah offer unique benefits in addressing the socio-economic needs. One of the key abilities of Islamic social finance instruments is innovation. Innovation in Islamic social finance practices was identified as a key driver to sustain the development of Islamic finance. Adapting to new market growth and opportunities is vital for institutions to thrive in a dynamic and competitive environment and enhance their effectiveness and impact. This study therefore identifies and maps zakat innovation research. The method used is a qualitative analysis using a systematic literature review to investigate research trends, major topics of interest, critical lessons learned and future research opportunities on Islamic social finance theme. The secondary data from the 30 selected articles from the year 2017-2024 were analyzed using the Nvivo 14 Plus software. The findings reveal that various focus of discussion and cluster analyses that describe research lines in Islamic social finance innovation include management, development, social welfare, system and SDGs. This study contributed to the enrichment of Islamic social finance literature. From a practical viewpoint, the study results can be used by institutions, regulators and government to improve the effectiveness of Islamic social finance instruments and determine required strategies.